The efficacy of a herbal-based toothpaste in the control of plaque and gingivitis: A clinico-biochemical study - George Jacob; Hegde Shashikant; Rajesh K; Kumar Arun (Wolters Kluwer Medknow Publications, 2009)
Objective: A double-blinded controlled clinical trial with parallel groups was designed to investigate the effectiveness of a herbal-based toothpaste in the control of plaque and gingivitis as compared with a conventional dentifrice. The efficacy of Colgate Herbal over Colgate tooth paste was assessed in this study. Materials and Methods: Thirty subjects with gingivitis participated in the study. All participants had at least 20 natural teeth with no probing depths greater than 3 mm and a plaque index score of 2 or more at baseline. At baseline, the clinical parameters like gingival index, plaque index and salivary pH were estimated. Paired t-test was used to compare the difference within the groups and unpaired t-test was used to compare the difference between the groups at baseline and on the 30 th day. Results: At the end of the study, there were statistically significant reductions in the gingival index and the plaque index scores within the test group. However, there were no statistically significant differences between the test and the control groups. The salivary pH changes were not statistically significant in the test group but were displaced more toward the acidic range in the control group. Conclusion: It was however concluded that the herbal-based toothpaste was as effective as the conventionally formulated dentifrice in the control of plaque and gingivitis.